Right paraduodenal hernia, rare cause of gangrene bowel: case report with review of literature - Kamat, Sanjivi; Cormoli, Gautam; Narsapur, Sudhir; Patil, Rajesh (International Surgery Journal, 2019)
A right paraduodenal hernia includes small bowel trapped within a peritoneal sac between the right and transverse colon, positioned right of midline, with the hernia sac opening to the left at the ligament of treitz, with either the superior mesenteric or ileo-colic artery at the anterior aspect of the sac. Patients with PDH often present with signs and symptoms of obstruction and/or bowel gangrene. We report a case of a 50 year old male presenting with small bowel ischaemia due to right paraduodenal hernia. Patient presented with chief complaints of colicky abdominal pain since two days and abdominal distension, and altered sensorium since one day. Abdominal ultrasonography showed dilated small bowel loops, and CT scan of abdomen was suggestive of clustering of small bowel loops with proximal dilatation. Exploratory laparotomy revealed a right PDH with a strangulated loop of 160 cm of small bowel within. The peritoneum at the ligament of Treitz was lax. The DJ flexure showed gangrenous changes along the anti-mesenteric edge. Resection and anastomosis of small bowel was done along with wedge resection of the DJ flexure, followed by feeding jejunostomy. The sac was opened up wide and plicated over itself to prevent recurrences. Perioperative course was uneventful, and patient discharged on post op day 10. Jejunostomy tube was removed after one week. Patient is being followed up at OPD level with close surveillance to prevent nutritional deficiency due to short gut syndrome. A vigilant mind is of utmost importance to suspect and diagnose paraduodenal hernia to limit morbidity and mortality.